Problems in the non-quantification of the monetary claims in the New Procedural Labor Act: Darkness and ambiguity - Bulnes Alegría, Iván (2020)
The New Procedural Labor Act has promoted the principles of orality and procedural economy, but a problem arises when monetary claims are promoted without expressing the amount of these. Such scenery creates a situation of ambiguity that allows the defendant to formulate an «exception», and thereby delay the process due to the negligence of the plaintiff. In this work, it is proposed that the plaintiff will be obliged to quantify the amount required at the relevant hearing, in order to allow the defendant to know this amount in a timely manner and not harm his right of defense.